Optimalisasi Kinerja U-Turn Di Ruas Jalan Sudirman Selatan Kota Pekanbaru Dengan Pendekatan PKJI 2023 Dan Vissim - Stefanus Sylvan Ryanto; Meynessa Puspita Tika Putri; Aswin Badarudin Atmajaya (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2026)
U-Turn Sudirman Selatan is located between segments 2 and 3 of Jalan Jenderal Sudirman, Pekanbaru City, which is famous for its congestion. Not only by observation, this is also proven by performance calculations through PKJI 2023 and a degree of saturation of 0.97 is obtained. The large volume of vehicles and the presence of large vehicles maneuvering on the u-turn are the causes of this problem. This study aims to optimize performance on the u-turn study. The method used by the author is PKJI 2023 and modeling through vissim. Meanwhile, the data needed is the busiest one-hour volume data on the u-turn, spotspeed, and also inventory. Based on the existing problems, the solution that can be applied is to redesign the geometry to increase capacity and make the u-turn one-way to break the conflict. Based on the results of the optimization analysis, an increase in performance was obtained in the form of a decrease in the degree of saturation by 18% at the north u-turn and 16% at the south U-Turn, a decrease in queue length by 73% at the north u-turn and 96% at the south u-turn. In addition, there was an increase in travel speed of 23% at the north u-turn and 21% at the south u-turn, as well as a decrease in average travel time by 52% at the north u-turn and 51% at the south U-Turn.